Nanotechnology in civil infrastructure a paradigm shift - Gopalakrishnan, Kasthurirangan; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
Nanotechnology in Civil Infrastructure is a state-of-the art reference source describing the latest developments in nano-engineering and nano-modification of construction materials to improve the bulk properties, development of sustainable, intelligent, and smart concrete materials through the integration of nanotechnology based self-sensing and self-powered materials and cyber infrastructure technologies, review of nanotechnology applications in pavement engineering, development of novel, cost-effective, high-performance and long-lasting concrete products and processes through nanotechnology-based innovative processing of cement and cement paste, and advanced nanoscience modeling, visualization, and measurement systems for characterizing and testing civil infrastructure materials at the nano-scale. Researchers, practitioners, undergraduate and graduate students engaged in nanotechnology related research will find this book very useful.
Multifunctional and Smart Carbon Nanotube Reinforced Cement-based Materials -- Applications of Nanotechnology in Road Pavement Engineering -- Application of Nanoscience Modeling to Understand the Atomic Structure of C-S-H -- The Effect of SWCNT and Other Nanomaterials on Cement Hydration and Reinforcement -- Nanomaterials-enabled Multifunctional Concrete and Structures -- Nano-Optimized Construction Materials by Nano-Seeding and Crystallization Control -- Next-Generation Nano-based Concrete Construction Products: A Review -- Optimization of Clay Addition for the Enhancement of Pozzolanic Reaction in Nano-modified Cement Paste -- Characterization of Asphalt Materials for Moisture Damage Using Atomic Force Microscopy and Nanoindentation -- Nanoclay-modified Asphalt Binder Systems Optimization of Clay Addition for the Enhancement of Pozzolanic Reaction in Nano-modified Cement Paste -- Characterization of Asphalt Materials for Moisture Damage Using Atomic Force Microscopy and Nanoindentation -- Nanoclay-modified Asphalt Binder Systems.
Electronic reproduction.
Keywords: Nanotechnology; Electronic books